The power of celebrity: Exploring the basis for Oprah's successful endorsement of Australia as a vacation destination. (April 2015) - Johns, Raechel; Weir, Brian; Weir, Ruth
In December 2010, Tourism Australia and Tourism New South Wales (respectively, Australia's national and Australia's largest state tourism promotion agencies) entered into an agreement with US talk show host Oprah Winfrey (or Oprah) for Ms Winfrey to undertake a celebrity endorsement tourism marketing campaign for Australia. In executing this campaign, Oprah and 300 of what she called her 'Ultimate Australia Adventure' viewers visited iconic and less well-known tourism attractions around Australia. These visits were filmed and later broadcast as four episodes of the Oprah Winfrey Show in the United States, Australia, and many other countries during January 2011. Longitudinal studies of subsequent visitation (especially from the United States) showed a delayed but significant surge in tourists, leading to Australian tourism authorities to mark the campaign a success. While celebrity endorsement has commonly been discussed in a marketing context, little attention has been given to celebrity endorsement in a tourism context (Glover (2009) Celebrity endorsement in tourism advertising: effects on destination image. Journal of Hospitality and Tourism Management 61(1): 16–23). This article investigates this issue, in particular, focussing on a close analysis of the content of the broadcasts to explore why the approach chosen for the campaign was successful. Results indicated that Oprah's celebrity endorsement of Australia positioned the Australian brand effectively. Oprah's 'brand image' had significant value as a celebrity endorser and that Oprah had strong appeal in these roles to the Tourism Australia target market.